Analysis of Conceptual Understanding Ability Among Students in the Mathematics Education Program Taking the Number Theory Course - Anisah, Anisah; Lastuti, Sri (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to analyze the conceptual understanding of students in the Mathematics Education Program with respect to the Number Theory course. The research method employed is quantitative descriptive analysis. The participants comprise 16 students in their second semester who enrolled in this course. The instrument utilized for the study is a written test consisting of descriptive questions designed to gauge conceptual understanding. The findings indicate that the average score for students' conceptual understanding in the Number Theory course is 64,75, which falls into the